Pengaruh Kebiasaan Konsumen Dan Preferensi Konsumen Sebagai Rencana Pengembangan Pasar PT. QL Agrofood Di Pasar Modern - Sujana, Sujana; Cahyani, Nani; Andriansyach, Anggie (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
Poultry industry in indonesia has experienced a fantastic growth during the last five years stable at double digit business growth. According to Indonesian Chicken Breeder Association (GPPU) Statistics: 1.6 bio DOC were produced in 2011 which represent an increase of 31% over 2010. Indonesia Feed Miller Association stated that indonesia produced 11.3 mio tons of poultry feed in 2011 and increase of 14% over 2010. One of the big issue of the category currently is that eggs and poultry products (meats, eggs, etc.) are currently treated and perceived as commodity. Consumer do not aware and do not care on further detail features of product. Simple physical properties and price are currently being the major of consideration when purchase teh product. The above fact becomes unfavorable issue from the company point of view, as it will lead to price war competition while the margin will be threaten down. Currently it is still perceived as functional driven category. QL AGROFOOD as a leading poultry company in Malaysia and currently on growing phase in indonesia, is eager to start brand building and category development in poultry products. Our ambition is to make another success story of poultry industry in Indonesia Keywords : Consumers' preference, market development